Odpowiedź :
[tex]\frac{r_1^{2}(p_1-p)}{r_2^{2}(p_2-p)} = \frac{t_1}{t_2}\\\\r_1^{2}(p_1-p)\cdot t_2 = r_2^{2}(p_2-p)\cdot t_1\\\\r_1^{2}p_1t_2-r_1^{2}pt_2 = r_2^{2}(p_2-p)t_1\\\\r_1^{2}p_1t_2 = r_1^{2}pt_2 +r_2^{2}(p_2-p)t_1 \ \ /:r_1^{2}t_2\\\\p_1 = \frac{r_1^{2}pt_2 + r_2^{2}(p_2-p)t_1}{r_1^{2}t_2}[/tex]
[tex]\underline{p_1 = p + \frac{r_2^{2}(p_2-p)t_1}{r_1^{2}t_2}}[/tex]
Odpowiedź:
[tex]p_{1}[/tex] = p + [tex]\frac{r_{2} ^{2} *(p_{2} -p)*t_{1}}{r_{1} ^{2} *t_{2}}[/tex]
Wyjaśnienie:
[tex]\frac{r_{1} ^{2} *(p_{1} -p)}{r_{2} ^{2} *(p_{2} -p)}[/tex] = [tex]\frac{t_{1} }{t_{2} }[/tex]
[tex]r_{1} ^{2} *(p_{1} -p)*t_{2} =[/tex] [tex]r_{2} ^{2} *(p_{2} -p)*t_{1}[/tex] /: ([tex]r_{1} ^{2} *t_{2}[/tex])
[tex](p_{1} -p)[/tex] = [tex]\frac{r_{2} ^{2} *(p_{2} -p)*t_{1}}{r_{1} ^{2} *t_{2}}[/tex]
[tex]p_{1}[/tex] = p + [tex]\frac{r_{2} ^{2} *(p_{2} -p)*t_{1}}{r_{1} ^{2} *t_{2}}[/tex]